Duration of Heightened Risk of Acute Ischemic Stroke After Hospitalization for Acute Systolic Heart Failure - Devin J. Burke; Tehniyat Baig; Parag Goyal; Hooman Kamel; Richa Sharma; Neal S. Parikh; Stephen A. McCullough; Cenai Zhang; Alexander E. Merkler (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background The duration and magnitude of increased stroke risk after a hospitalization for acute systolic heart failure (HF) remains uncertain. Methods and Results The authors performed a retrospective cohort study using claims (2008–2018) from a nationally representative 5% sample of Medicare beneficiaries aged ≥66 years. Cox regression models were fitted separately for the groups with and without acute systolic HF to examine its association with the incidence of ischemic stroke after adjustment for demographics, stroke risk factors, and Charlson comorbidities. Corresponding survival probabilities were used to compute the hazard ratio (HR) in each 30‐day interval after discharge. The authors stratified patients by the presence of atrial fibrillation (AF) before or during the hospitalization for acute systolic HF. Among 2 077 501 eligible beneficiaries, 94 641 were hospitalized with acute systolic HF. After adjusting for demographics, stroke risk factors, and Charlson comorbidities, the risk of ischemic stroke was highest in the first 30 days after discharge from an acute systolic HF hospitalization for patients with AF (HR, 2.4 [95% CI, 2.1–2.7]) and without AF (HR, 4.6 [95% CI, 4.0–5.3]). The risk of stroke remained elevated for 60 days in patients with AF (HR, 1.4 [95% CI, 1.2–1.6]) and was not significantly elevated afterward. The risk of stroke remained significantly elevated through 330 days in patients without AF (HR, 2.1 [95% CI, 1.7–2.7]) and was no longer significantly elevated afterward. Conclusions A hospitalization for acute systolic HF is associated with an increased risk of ischemic stroke up to 330 days in patients without concomitant AF.